Linking Language Proficiency to Teaching Competence: A Case Study of EFL Teachers in Indonesia - Rachmawati, Dwita Laksmita; Purwati, Oikurema (Elsya : Journal of English Language Studies, 2021)
In Indonesia, English teachers and lecturers have to pass specific number of TOEFL score as a passing card to carry out teaching activity. Yet, there is no further observation from researchers or government about how much the English teachers’ proficiency affects the classroom instruction capability. Hence, this research is worth pursuing to reveal information for teachers’ professional development. This study is a case study that aims to gather information about the relation between English teachers’ proficiency and teaching skills. The data were obtained from semi-structured interview and class observation. To analyse the data, the researchers coded the data manually to eliminate errors. There are two English lecturers from one private University in Malang, East Java, Indonesia as the participants of this study. They were selected purposefully based on their level of general proficiency in English. This study revealed that high level of English proficiency alone cannot be a single indicator for conducting effective English teaching and learning process. Teachers need to obtain both high level of language proficiency and own pedagogical skills to provide optimised learning and teaching environment. This research is seen as a fundamental framework for teachers to improve their English teaching perseverance.